2019
DOI: 10.1371/journal.pgen.1008002
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Cdkn1b in ACI rats leads to increased proliferation and pregnancy-associated changes in the mammary gland due to perturbed systemic endocrine environment

Abstract: Mammary epithelial progenitors are the normal cell-of-origin of breast cancer. We previously defined a population of p27 + quiescent hormone-responsive progenitor cells in the normal human breast whose frequency associates with breast cancer risk. Here, we describe that deletion of the Cdkn1b gene encoding the p27 cyclin-dependent kinase inhibitor in the estrogen-induced mammary tumor-susceptible ACI rat strain leads to a decrease in the relative frequencies of Cd4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Of the 13 somatic mutations (Figure 1A, see long lines) that we identified in LBC solid biopsies, four generated a stop codon and resulted in the loss of p27 C‐terminus. This observation confirmed the higher frequency of truncating/frame shift mutations among the different mutations that were observed in sporadic breast cancer [7,8] (Figure 1A, see short lines) and supported the possibility that truncation of p27 C‐terminus directly contributes to onset and/or progression of breast cancer, as we and others have recently proposed [12,28,36–38].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Of the 13 somatic mutations (Figure 1A, see long lines) that we identified in LBC solid biopsies, four generated a stop codon and resulted in the loss of p27 C‐terminus. This observation confirmed the higher frequency of truncating/frame shift mutations among the different mutations that were observed in sporadic breast cancer [7,8] (Figure 1A, see short lines) and supported the possibility that truncation of p27 C‐terminus directly contributes to onset and/or progression of breast cancer, as we and others have recently proposed [12,28,36–38].…”
Section: Resultssupporting
confidence: 86%
“…Consistent with this, p27 deficiency in mice was associated with hypoplasia, impaired ductal branching and lobulo‐alveolar differentiation [40], a phenotype consistent with a putative role for p27 in regulating the number and proliferation of mammary epithelial progenitors. Of note, we and others have observed that an absence of p27 in Cdkn1b −/− female animals induces dramatic changes in mammary epithelial cells, probably due to altered hormonal signaling and perturbed endocrine environment [38] (G Mungo, personal communication October 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the sequence of events and the interaction between the individual molecular players await further scrutiny, other studies lend support to the present findings. Thus, the regulation of p27 + hormone-responsive progenitors in human normal breast has been suggested as a marker of breast cancer risk 11 , and more specifically, deletion of Cdkn1b in rats leads to generation of a higher proportion of mature mammary luminal cells 23 , further implicating the pool size of hormone-responsive luminal progenitors in breast cancer risk. The role of S100A7 in normal breast also remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Here on, we will describe what has been revealed about the importance in mediating distinct biological aspects of PR signaling function in vivo. Of note, the rat model was used to identify PR targets by ChIP-seq and revealed that networks relating to cell cycle and FGF and ErbB signaling were enriched (Ding et al, 2019).…”
Section: Cell Intrinsic and Paracrine Signalingmentioning
confidence: 99%